MultiNet: Connecting to Multiple IEEE 802.11 Networks Using a Single Wireless Card - Bahl, Victor; Bahl, Pradeep; Chandra, Ranveer (2003)
There are a number of scenarios where it is desirable to have a wireless device connect to multiple networks simultaneously. Currently, this is possible only by using multiple wireless network cards in the device. Unfortunately, using multiple wireless cards causes excessive energy drain and consequent reduction of lifetime in battery operated devices. In this paper, we propose a software based approach, called MultiNet, that facilitates simultaneous connections to multiple networks by virtualizing a single wireless card. The wireless card is virtualized by introducing an intermediate layer below IP, which continuously switches the card across multiple networks. The goal of the switching algorithm is to be transparent to the user who sees her machine as being connected to multiple networks. We present the design, implementation, and performance of the MultiNet system.We analyze and evaluate buffering and switching algorithms in terms of delay and energy consumption. Our system has been operational for over twelve months, it is agnostic of the upper layer protocols, and works well over popular IEEE 802.11 wireless LAN cards.